The validity, effectiveness, and enforceability of arbitration agreements: issues and solutions - Кравцов, Сергій Олександрович; Кравцов, С. О.; Кравцов, Сергей Александрович; Kravtsov, Serhii O.; Сурженко, Ольга Анатоліївна; Сурженко, О. А.; Сурженко, Ольга Анатольевна; Surzhenko, Olha A.; Голубєва, Неллі Юріївна; Голубєва, Н. Ю.; Голубева, Нелли Юрьевна; Holubieva, Nelli Yu.; et al. (AJEE, 2021)
The main reason for dispute in international commercial arbitration is the existence of an arbitration agreement concluded between the parties to a foreign trade agreement. The procedure of dispute resolution in international commercial arbitration will depend on the extent to which this arbitration agreement is concluded correctly in accordance with the norms of international and national law. Quite often, in the law enforcement activities of both national courts and arbitrations, there are questions about the validity, effectiveness, and enforceability of an arbitration agreement. In different countries, this issue is addressed ambiguously. In one case, national law takes precedence, and, accordingly, national courts are empowered to consider the validity, effectiveness, and enforceability of an arbitration agreement. In other cases, however, the autonomy of the arbitration agreement is a priority aspect of the consideration of any procedural issues by international commercial arbitration as the only and indisputable body authorised by the parties to the foreign trade agreement to consider a particular dispute. The article analyses doctrinal and legislative approaches to this issue, in which the authors come to the logical conclusion that national courts do not consider the validity, effectiveness, and enforceability of an arbitration agreement.

Основною причиною спору в міжнародному комерційному арбітражі є наявність арбітражної угоди, укладеної між сторонами зовнішньоекономічного договору. Порядок вирішення спорів у міжнародному комерційному арбітражі буде залежати від того, наскільки дана арбітражна угода буде укладена правильно відповідно до норм міжнародного та національного права. Досить часто в правоохоронній діяльності як національних судів, так і арбітражів виникають питання щодо дійсності, ефективності та можливості виконання арбітражної угоди. У різних країнах це питання вирішується неоднозначно. В одному випадку перевагу має національне законодавство, і, відповідно, національні суди мають право розглядати дійсність, ефективність та можливість виконання арбітражної угоди. Однак в інших випадках автономія арбітражної угоди є пріоритетним аспектом розгляду будь-яких процесуальних питань міжнародним комерційним арбітражем як єдиним і безспірним органом, уповноваженим сторонами зовнішньоекономічного договору розглядати конкретний спір. У статті проаналізовано доктринальні та законодавчі підходи до цього питання, у яких автори приходять до логічного висновку, що національні суди не враховують дійсність, ефективність та можливість виконання арбітражної угоди.
Kravtsov S. The validity, effectiveness, and enforceability of arbitration agreements: issues and solutions / S. Kravtsov, O. Surzhenko, N. Golubeva // Access to justice in Eastern Europe. - Iss. 4. - AJEE, 2021. - P. 116-130.
Keywords: international commercial arbitration; arbitration agreement; autonomy of arbitration agreement; міжнародний комерційний арбітраж; арбітражна угода; автономія арбітражної угоди; Research Subject Categories::LAW/JURISPRUDENCE